FACTORS AFFECTING EARNING MANAGEMENT ON TRANSPORTATION CORPORATIONS IN INDONESIA - Arnas, Yenni; Lamtiar, Suse; Kurniawati, Zulina; Kurnianto, Benny; Kalbuana, Nawang (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The management of earnings or Earnings Management defined as management activities for adjusting earnings according to specific objectives. Therefore, empirical evidence showing the impact of Institutional and managerial Ownership, intellectual capital, audit quality on income management is necessary. 14 transportation companies listed on the Indonesian stock exchange were surveyed in accordance with the research criteria. A purposeful sampling method collected data. The SPSS 23 application tests the multiple linear regression hypothesis. Of the variables used in this study, only intellectual capital has a positive impact on profit management and can be used as one of the indicators in future research to measure income management actions.